Ecological Worldview as the Central Component of Environmental Concern: Clarifying the Role of the NEP. Issue 1 (2nd January 2019) - Xiao, Chenyang; Dunlap, Riley E.; Hong, Dayong
Abstract: This study examines whether an ecological worldview—operationalized by the New Ecological Paradigm (NEP) Scale--serves as the source of coherence of Environmental Concern (EC). Using data on four samples from the 1992 Gallup "Health of the Planet" Survey and the 2003 and 2010 Chinese General Social Surveys, we found that in all samples not only is the NEP the most powerful predictor of EC, but it also mediates the effects of socio-demographic variables on EC as hypothesized. The results confirm that the NEP is the source of coherence of EC, making it a meaningful construct.